Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-6 Factoring ax(squared) + bx + c - Mixed Review - Page 510: 64



Work Step by Step

In order to simplify $(a+9)^{2}$ we must apply the rule that states that $(x+y)^{2}$=$x^{2}$+2xy+$y^{2}$, and we'll set x=a and y=9. Therefore, $(a+9)^{2}$=$a^{2}$+2(a)(9)+$9^{2}$ =$a^{2}$+18a+81
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.